The emergence of microeconomics - Ramesh, Sangaralingam (Henry Stewart Talks, 2018)
The two branches of economics, Economic analysis and economic activities, Greek philosophers’ contributions to microeconomics, The paradox of value, Theories of value and the marginal revolution